Pulmonary hypertension before and after balloon mitral Valvuloplasty - Indrajit Mandal (International Journal of Medical Research and Review, 2017)
Objective: To testify effectiveness of BMV in mitral stenosis to resolve pulmonary hypertension.Material and Method: The study was conducted at N.R.S Medical College and Hospital over 18 months with 39 patients of severe mitral stenosis with pulmonary hypertension. They were followed up at 48hours, 1 month and 6 month after BMV.Result: 20.51% patients had mild, 41.02% patients had moderate and 38.46% patients had severe pulmonary hypertension before BMV. Mean mitral valve area before and after BMV were 0.89±0.11cm and 1.89±0.21cm respectively. Mean transmitral gradient was 15.43±2.3mm 0f Hg before and 7. 86±2.25 mm of Hg after BMV. On 3rd day, before discharge PASP became normal in 1 patient in mild group although improvement was not statistically significant (p=0.234) but statistically significant improvement of PSBP was seen in both moderate and severe groups (p=0.001). At 1m follow up PASP came down to normal in 3 patients of mild group (p=0.106). 5 of moderate and 1 patient of severe groups also improved to have PSBP ˂25 mm of Hg, the finding was statistically significant in both groups (p=0.001). The improvement in all three groups at final check up at 6m was statistically significant (p=0.001). 5 patients in each mild and moderate and 2 in severe group were found to have normal PASP.Conclusion: In spite of significant risk, BMV is worth doing in patients with pulmonary hypertension due to mitral stenosis as there is not only dramatic relief of PH of cardiac causes but also improvement of PH due to pulmonary pathology to some extent.